2016
DOI: 10.1016/j.eplepsyres.2016.04.001
|View full text |Cite
|
Sign up to set email alerts
|

Low functional robustness in mesial temporal lobe epilepsy

Abstract: Objectives Brain functional topology was investigated in patients with mesial temporal lobe epilepsy (mTLE) by means of graph theory measures in two differentially defined graphs. Measures of segregation, integration, and centrality were compared between subjects with mTLE and healthy controls (HC). Methods Eleven subjects with mTLE (age 36.5 ± 10.9 years) and 15 age-matched HC (age 36.8 ± 14.0 years) participated in this study. Both anatomically and functionally defined adjacency matrices were used to inves… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
14
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 52 publications
4
14
0
Order By: Relevance
“…Our findings are consistent with previous studies reporting functional abnormalities in brain networks of patients with epilepsy compared to healthy control subjects. For instance, Garcia-Ramos et al observed that the functional brain network in patients with mesial temporal lobe (mTLE) epilepsy presented lower segregation than healthy control subjects, which may be an indication of decreasing robustness and increasing disruption in brain networks of patients with epilepsy ( Garcia-Ramos et al, 2016 ). Another study reported a lower modularity and higher global efficiency in TLE patients compared to healthy controls ( Doucet et al, 2015 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Our findings are consistent with previous studies reporting functional abnormalities in brain networks of patients with epilepsy compared to healthy control subjects. For instance, Garcia-Ramos et al observed that the functional brain network in patients with mesial temporal lobe (mTLE) epilepsy presented lower segregation than healthy control subjects, which may be an indication of decreasing robustness and increasing disruption in brain networks of patients with epilepsy ( Garcia-Ramos et al, 2016 ). Another study reported a lower modularity and higher global efficiency in TLE patients compared to healthy controls ( Doucet et al, 2015 ).…”
Section: Discussionmentioning
confidence: 99%
“…Graph measures can extract useful features from the brain network ( Bullmore and Sporns, 2009 ). Network topology has been used to characterize structural and functional properties of the brain networks in healthy subjects and patients ( Ridley et al, 2015 ; Garcia-Ramos et al, 2016 ; Rubinov and Sporns, 2010 ). The brain of a healthy subject is a complex network and has properties such as balanced integration and segregation; however, the brain of patients with epilepsy is deviated toward regular or random networks, with alterations in integration and segregation characteristics.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…11 The wide range of studies of genetic, signaling, communications, computation, and neural networks indicated that the structural organization of the human brain has a small-world topology that maximizes simultaneous local and global information processing. 34 The strengths of this study include its relatively large sample size (total of 150 subjects) and comparison according to the duration of epilepsy. The patients with focal epilepsy exhibited a decrease in mean clustering coefficient, characteristic path length, small-worldness, and global efficiency compared with healthy subjects.…”
Section: Discussionmentioning
confidence: 99%
“…The considerably lower segregation could translate into a network that lacks the capacity to contain functional processes into a specific community, such as memory or language, within the brain making it less specialized, whereas high integration may be interpreted by epileptic networks that are more tightly connected, which can be related to enhanced neural synchronization and seizure propagation. 34 The strengths of this study include its relatively large sample size (total of 150 subjects) and comparison according to the duration of epilepsy. In addition, we did graph theoretical analysis based on DTI, which directly reveled the structural connections and had high reproducibility.…”
Section: It Alsomentioning
confidence: 99%